Continuous electrochemical treatment of simulated industrial textile wastewater from industrial components in a tubular reactor - Körbahtia, B.K.; Tanyolac, A.
The continuous electrochemical treatment of industrial textilewastewater in a tubular reactorwas investigated. The synthetic wastewater was based on the real process information of pretreatment and dyeing stages of the industrial mercerized and non-mercerized cotton and viscon production. The effects of residence time on chemical oxygen demand (COD), color and turbidity removals and pH changewere studied under response surface optimized conditions of 30 .C, 25 g/L electrolyte concentration and 3505 mg/L COD feed concentration with 123.97mA/cm2 current density. Increasing residence time resulted in steady profiles of COD and color removals with higher treatment performances. The best column performance was realized at 3 h of residence time as 53.5
Keywords: ELECTROCHEMICAL WASTEWATER TREATMENT; TEXTILE WASTEWATER; TUBULAR REACTOR; MASS TRANSFER; ENERGY CONSUMPTION